The Role of VP1 Amino Acid Residue 145 of Enterovirus 71 in Viral Fitness and Pathogenesis in a Cynomolgus Monkey Model - Kataoka, Chikako; Suzuki, Tadaki; Kotani, Osamu; Iwata-Yoshikawa, Naoko; Nagata, Noriyo; Ami, Yasushi; Wakita, Takaji; Nishimura, Yorihiro; Shimizu, Hiroyuki (PLoS pathogens, 2015)
Enterovirus 71 (EV71), a major causative agent of hand, foot, and mouth disease, occasionally causes severe neurological symptoms. We identified P-selectin glycoprotein ligand-1 (PSGL-1) as an EV71 receptor and found that an amino acid residue 145 in the capsid protein VP1 (VP1-145) defined PSGL-1-binding (PB) and PSGL-1-nonbinding (non-PB) phenotypes of EV71. However, the role of PSGL-1-dependent EV71 replication in neuropathogenesis remains poorly understood. In this study, we investigated viral replication, genetic stability, and the pathogenicity of PB and non-PB strains of EV71 in a cynomolgus monkey model. Monkeys were intravenously inoculated with cDNA-derived PB and non-PB strains of EV71, EV71-02363-EG and EV71-02363-KE strains, respectively, with two amino acid differences at VP1-98 and VP1-145. Mild neurological symptoms, transient lymphocytopenia, and inflammatory cytokine responses, were found predominantly in the 02363-KE-inoculated monkeys. During the early stage of infection, viruses were frequently detected in clinical samples from 02363-KE-inoculated monkeys but rarely in samples from 02363-EG-inoculated monkeys. Histopathological analysis of central nervous system (CNS) tissues at 10 days postinfection revealed that 02363-KE induced neuropathogenesis more efficiently than that induced by 02363-EG. After inoculation with 02363-EG, almost all EV71 variants detected in clinical samples, CNS, and non-CNS tissues, possessed a G to E amino acid substitution at VP1-145, suggesting a strong in vivo selection of VP1-145E variants and CNS spread presumably in a PSGL-1-independent manner. EV71 variants with VP1-145G were identified only in peripheral blood mononuclear cells in two out of four 02363-EG-inoculated monkeys. Thus, VP1-145E variants are mainly responsible for the development of viremia and neuropathogenesis in a non-human primate model, further suggesting the in vivo involvement of amino acid polymorphism at VP1-145 in cell-specific viral replication, in vivo fitness, and pathogenesis in EV71-infected individuals.